Parasitism of stink bug eggs(Hemiptera: Pentatomidae) of soybean fields in the Triangulo Mineiro; Minas Gerais, Brazil - Venzon, Madelaine (1999)
A survey of the seasonal occurrence of stink bug egg parasitoids was carried out in soy bean fields in the Triangulo Mineiro region, Minas gerias state Brazil